Shark Side of the Moon: Are Shark Attacks Related to Lunar Phase? - French, Lindsay A.; Midway, Stephen R.; Evans, David H.; Burgess, George H. (Frontiers in Marine Science, 2021)
Animals across taxa have shown behaviors linked to moon phase (or the proxy of lunar illumination), and marine organisms are well-documented to calibrate certain activities with the moon. Few studies have looked at a possible connection between moon phase and shark attacks on humans, and the results have been preliminary or lacking relationships. We used nearly 50 years of shark attack data from across the globe to test for a relationship between shark attacks and moon phase. We examined factors of geography, shark species, and outcome of attack. From 12 relationships that we tested (totaling 120 comparisons), we found 12 significant outcomes, of which five were positive (i.e., more attacks than expected) and seven were negative (i.e., fewer attacks than expected). Specifically, all the instances of more shark attacks than expected occurred at lunar illumination >50%, while all the instances of fewer shark attacks than expected occurred at lunar illumination of <50%. The findings presented here provide global evidence that shark attacks may be related to moon phase, and such information could be useful toward evaluating attack risk and developing recommendations for water-based recreational activities.